Creative Crafts and Stitchery - Dooley D. (USA Meredith Corporation, 1976)
146 exciting projects you can make yourself. Complete how-to for embroidery, weaving, crochet, knitting, needlepoint, applique, framing, and woodworking. 288 pages of impressive craft and stitchery projects that will stir your creative impulses to immediate action. Whether or not you've ever worked with yarn, fabric, wood, metal, feathers, rocks, flowers, or plastic, you'll find a multitude of designs tailored to your tastes and talents.
Keywords: 7 . - . .